2022
DOI: 10.1021/acs.cgd.2c00241
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop Electrochemical Growth and Controlled Alloying of Polycrystalline InxGa1–xAs Thin Films

Abstract: Compared to Si, GaAs offers unique material advantages such as high carrier mobility and energy conversion efficiency, making GaAs a leading competitor to replace Si on several technological fronts related to optoelectronics and solar energy conversion. Alloying the GaAs lattice with elemental In allows the direct bandgap of the resulting ternary alloy to be tuned across the near-infrared (NIR) region of the electromagnetic spectrum from ∼0.9 to 3.5 μm. However, methods of fabricating high-quality crystalline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For example, it has been shown that alloying it with indium atoms makes it possible to create the ternary compound In x Ga 1−x As [31]. The more indium in the compound, the more we observe a shift of the electromagnetic spectrum in the infrared region of the spectrum to a minimum value of 0.354 eV [32]. This expands the application of InxGa 1-x As, particularly as materials for infrared optics [33].…”
Section: Introductionmentioning
confidence: 84%
“…For example, it has been shown that alloying it with indium atoms makes it possible to create the ternary compound In x Ga 1−x As [31]. The more indium in the compound, the more we observe a shift of the electromagnetic spectrum in the infrared region of the spectrum to a minimum value of 0.354 eV [32]. This expands the application of InxGa 1-x As, particularly as materials for infrared optics [33].…”
Section: Introductionmentioning
confidence: 84%